Hubungan Antara Gunung Dengan Krisis Lingkungan Makhluk Hidup (Studi Tematik Tafsir Al-Misbah) - Tantery Chandrika Sari; Muzakkir Muzakkir; Ahmad Perdana Indra (CV. ITTC INDONESIA, 2025)
This study examines how mountains are related to the environmental crisis facing living creatures. Mountains serve as a balancing force in the natural environment; without them, nature would be thrown into turmoil. The Qur'an clearly explains the usefulness of mountains, including their contents and their role as a repository for sources of life, such as mining products. In addition, mountains are also described as giant water tanks capable of holding enormous amounts of water. Exploiting natural resources from mountains can provide many benefits for living creatures, but if done excessively, it can also have a significant negative impact on the environment and society. From this background, the main themes in the problem formulation are as follows: How do mountains influence the environmental crisis of living creatures? 1) How are mountains utilized? 2) How can nature be preserved? 3) Which verses discuss mountains? 4) What are the impacts of damaging the environment? 5) How does Al-Misbah interpret the relationship between mountains and the environment of living creatures? This study is a library research that uses Tafsir Al-Misbah as its primary source. The method used in this study is thematic interpretation. From the results of this study, the author finds that mountains play a very important role in the environment. As humans, we must always protect our environment so that it remains preserved.